2011
DOI: 10.15835/nsb315463
|View full text |Cite
|
Sign up to set email alerts
|

Light Absorption and Carotenoid Synthesis of Pot Marigold (Calendula officinalis L.) in Response to Phosphorous and Potassium Varying Levels

Abstract: In order to provide additional information on the effects of elemental deficiency on factors that affect plant production in medicinal plants, a factorial field experiment as randomized complete block design was conducted on Calendula officinalis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Each value is the mean of triplicates sample ± S.E. Similar responses to stress conditions were reported in soybean [69] and marigold [55]. Plants have developed the scavenging mechanism of ROS categorized as enzymatic and non-enzymatic defense system.…”
Section: Resultssupporting
confidence: 55%
See 1 more Smart Citation
“…Each value is the mean of triplicates sample ± S.E. Similar responses to stress conditions were reported in soybean [69] and marigold [55]. Plants have developed the scavenging mechanism of ROS categorized as enzymatic and non-enzymatic defense system.…”
Section: Resultssupporting
confidence: 55%
“…Under drought conditions (Table 2), increases in quantities of carotenoids and non-enzymatic antioxidants were reported in many studies [53,54]. For instance, the results obtained by Sedghi et al [55] showed that, the concentration of carotenoids; namely lycopene and β-carotene, increased under water deficit in Calendulla officinalis compared with control plants. Similarity, carotenoids were accumulated in drought-stressed Rosmarinus officinalis [56].…”
Section: Resultsmentioning
confidence: 90%
“…Carotenoids (Car) are auxiliary pigments essential for photosynthesis, and their response to drought is somewhat different from that of Chl. Many studies have shown that drought increases Car content (Sedghi et al, 2012;Saeidnia et al, 2018), and plants of droughttolerant genotypes maintain higher Car content than droughtsensitive genotypes under drought (Shah et al, 2011). It has also been reported that drought significantly reduces Car content (Mibei et al, 2017;Khodabin et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids, carotenoids and polyphenols are the active ingredient contents reported previously for C.officinalis flowers (Bunghez and Ion, 2011;Lim, 2014). The most essence in this plant is formed at full blooming (0.97%) and the least of essence (0.13%) before flowering (Sedghi et al 2011).…”
mentioning
confidence: 51%